2019
DOI: 10.1155/2019/4232730
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Load Weight on Dynamic Response of Vibrating Screen

Abstract: The dynamic response of the vibrating screen has a great impact on the screening efficiency and fatigue life of the structures. For the conventional dynamic design, the consideration of the influence of load weight on dynamic response is lacking. So, in this paper, taking a very common vibrating screen used in tunnel construction as an example, the relationship between the screen dynamic response and the load weight is studied through numerical simulations. Firstly, to make sure the accuracy of simulation, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Design engineers must consider the static and dynamic geomechanical characteristics of soils and rocks. This includes evaluation of stability of dam slopes during excavations [1], foundation dynamic responses [2], earthquake reliance [3], dynamic strength of rocks in concrete [4] and rocks around tunnels [5], safety of underground mines [6], rock cutting and blasting [7,8], buildings on limestone sands [9], as well as estimation of reservoir permeability [10].…”
Section: Introductionmentioning
confidence: 99%
“…Design engineers must consider the static and dynamic geomechanical characteristics of soils and rocks. This includes evaluation of stability of dam slopes during excavations [1], foundation dynamic responses [2], earthquake reliance [3], dynamic strength of rocks in concrete [4] and rocks around tunnels [5], safety of underground mines [6], rock cutting and blasting [7,8], buildings on limestone sands [9], as well as estimation of reservoir permeability [10].…”
Section: Introductionmentioning
confidence: 99%
“…Failure diagnosis requires accurate dynamic modeling and system identification [6]. In recent years, many studies have reported on the dynamic modeling [7][8][9][10], dynamic design [11][12][13][14], dynamic optimization [15][16][17][18][19][20], particle motion analysis [21][22][23][24], and spring failure diagnosis of vibrating screens [25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…The essence of screening is to apply a small amplitude and suitable vibrational frequency to make the particles bounce and filter smaller particles under the screen [5]. Therefore, the key problem of the screening process is the dynamic behavior of the particles on the vibrating screen.…”
Section: Introductionmentioning
confidence: 99%